Generative AIs in Detecting Mpox Related Misinformation: ChatGPT and Gemini - Corraya, Badhan Hubert; Khan, Miron; Mahmud, Md. Rifat (The Indonesian Journal of Communication Studies, 2024)
This study investigates the performance of two generative AI systems, ChatGPT and Gemini, in detecting Mpox-related misinformation. As the Mpox outbreak in recent times led to widespread dissemination of both accurate and false information, particularly on social media platforms, the potential of AI in combating health misinformation has gained attention. The research presented ten commonly circulated pieces of Mpox misinformation to both AI systems, evaluating their responses against fact-checks and public health databases. Results demonstrated that both ChatGPT and Gemini performed admirably in identifying false information and providing accurate data about Mpox. Their responses aligned closely with authoritative sources such as the World Health Organization and Centers for Disease Control and Prevention. The study's findings suggest that these AI tools could be valuable assets in combating the spread of misinformation during disease outbreaks. However, the researchers emphasize that AI systems should not be considered infallible and should be used in conjunction with human expertise and authoritative sources. The performance of ChatGPT and Gemini in this context aligns with broader trends of generative AI platforms showing potential across various fields, including science and medicine. While promising, the study calls for further research to fully realize the potential of AI chatbots in addressing health misinformation, including investigations into practical applications such as integrating AI systems into public health communication strategies or developing AI-assisted fact-checking tools for social media platforms.